Quilling Paper Stamp for the Efficiency of the Batik Production Process - Timbul Raharjo; Yulriawan Dafri (Budapest International Research and Critics University, 2022)
Batik is making motifs on cloth with a coloring system using a wax barrier. The United Nations Educational, Scientific and Cultural Organization (UNESCO) notes batik as a cultural heritage. Batik is one of the traditional cultural characteristics of Indonesia. Batik work has become a traditional skill for some Indonesian people. Batik is currently produced by many craftsmen in several regions in Indonesia. There are several types of batik, one of which is the stamping technique, namely the technique of making batik motifs by stamping wax on the fabric. The stamp technique aims to produce batik motifs automatically bulk. With a tool in the form of a batik stamp, you can speed up the batik production process. Batik stamp tools generally use tools made of copper metal. This material in the procurement process is relatively expensive. This paper aims to improve the efficiency of batik products by applying quilling paper stamp batik as an alternative tool that is cheap and easy to make to assist the batik production process. Quilling paper stamp batik can provide benefits for Micro, Small and Medium Enterprises (MSMEs) in the batik production process. Because batik cap made of copper requires relatively complicated materials and the manufacturing process. In this paper, qualitative methods are used by exploring batik motifs and batik paper stamp quilling tools in one pattern unit, namely applying batik stamp quilling paper tools. Quilling paper stamp batik can be a new alternative as a tool in batik production. Quilling paper batik stamp has the advantage of being more economical and efficient. Production and diversification of batik motifs are more varied. It is hoped that the batik industry will experience an increase in the production of fitas and the economy of the batik industry in Indonesia is increasing.